PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PBL BERBANTUAN GEOGEBRA: DEVELOPMENT OF PBL-BASED MATHEMATICS LEARNING TOOLS USING GEOGEBRA - Gabriella Buria; Rahmatullah Bin Arsyad; Arie Anang Setyo (Universitas Muhammadiyah Sorong, 2024)
Mathematics education in the era of globalization and the Industrial Revolution 4.0 requires an approach that can foster critical thinking, creativity, and problem-solving skills. Problem-based learning (PBL) is one of the learning strategies that can stimulate these abilities but requires appropriate learning tools to increase its effectiveness. GeoGebra, as a mathematical visualization tool, can support the implementation of PBL by providing dynamic and interactive simulations of mathematical concepts. This study aims to develop a PBL-based mathematics learning tool supported by GeoGebra to improve students' understanding of mathematical concepts. This type of research is R&D using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The analysis process is carried out by identifying the needs of device development and analyzing the curriculum, and student characteristics. The design and development stages produce RPS and LKM, which experts have validated and applied to three learning meetings. This study shows valid, practical, and effective results from the devices that have been developed. Based on these results, PBL and GeoGebra-based learning tools can be innovative solutions in mathematics learning to develop critical thinking skills and students' conceptual understanding.